2022
DOI: 10.11646/palaeoentomology.5.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Steinkern spiders: A microbial mat-controlled taphonomic pathway in the Oligocene Aix-en-Provence Lagerstätte, France

Abstract: The Aix-en-Provence Formation is an Oligocene (22.5 Ma) Lagerstätte in southern France that contains an abundance of soft-bodied fossils preserved in exceptional detail. Many taxa have been described from this formation, including insects, spiders, fishes, and plants, suggesting a diverse ecosystem in a subtropical, brackish, lacustrine paleoenvironment. Fossil spiders from this deposit are preserved as compression fossils and internal and external molds. Recently, compression fossils of spiders from Aix-en-Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Optical (light) Microscopy helps in visualizing the fine details of an object by creating a magnified image through a series of glass lenses. Optical microscopy has been widely used in the study of concretions (e.g., Iniesto et al, 2015 ; Dias and Carvalho, 2022 ; Downen et al, 2022 ; Lin et al, 2023 ).…”
Section: Analytical Methods For Concretion Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical (light) Microscopy helps in visualizing the fine details of an object by creating a magnified image through a series of glass lenses. Optical microscopy has been widely used in the study of concretions (e.g., Iniesto et al, 2015 ; Dias and Carvalho, 2022 ; Downen et al, 2022 ; Lin et al, 2023 ).…”
Section: Analytical Methods For Concretion Characterizationmentioning
confidence: 99%
“…This technique can be used to identify structures in fixed and living biological samples ( Lichtman and Conchello, 2005 ; Sanderson et al, 2014 ), and helps in understanding the viability of living and dead bacterial cells, biofilms, EPS and calcium carbonate precipitates ( McMullan, 1995 ; Vernon-Parry, 2000 ). This technique has been recently utilized for investigation of internal architecture in steinkern spider fossils from Oligocene Aix-en-Provence Lagerstätte in southern France ( Downen et al, 2022 ), which identified prolific microbial mat communities as likely being responsible for the preservation of infilled spider molds.…”
Section: Analytical Methods For Concretion Characterizationmentioning
confidence: 99%
“…1.5 m thick of very delicate and thin laminites. Its stratigraphy was extensively studied by Nel (1991) and Peinado (2002) who indicated that the laminites were generated by microbial mat activities, a result that was later confirmed by Downen et al (2022) when studying fossil Arachnida. The layer which has yielded the new fossil originates is very particular, being very rich in Silica, green-colored, with numerous dragonfly larvae, marine fishes, and Siphonophora, suggesting a putative marine influence at least in this Western part of the paleolake (Nel et al, 1987;Nel, 1991).…”
Section: Geological Settingmentioning
confidence: 96%